Determining the relationship of food neophobia, digital addiction, body image perception on social media with dietary inflammatory index among adolescents - Albayrak, Rumeysa; Demirel Ozbek, Yagmur (Frontiers in Public Health, 2025)
BackgroundAdolescence is a critical period in which both physical and psychological development accelerates and foundational dietary behaviors are established. This study aims to examine the relationships of food neophobia, digital addiction, body image perception on social media with the dietary inflammatory index (DII) among high school adolescents.MethodThis cross-sectional and descriptive study was conducted with a total of 354 high school students, including 200 females and 154 males. Data were collected through questionnaires and face-to-face interviews. The questionnaire included sections on general information, dietary habits, the Food Neophobia Scale (FNS), the Child and Adolescent Digital Addiction Scale (CADAS), the Appearance-Related Social Media Consciousness Scale (ASMC), and a 3-day dietary intake record. Data analysis was performed using IBM SPSS version 25.ResultsThe mean DII score was 3.23 ± 1.66, the mean FNS score was 38.33 ± 10.81, the mean CADAS score was 35.82 ± 11.53, and the mean ASMC score was 41.31 ± 17.71. Participants who skipped meals had significantly higher DII, CADAS, and ASMC scores (p < 0.05). Regular breakfast consumption was associated with lower DII and CADAS scores (p < 0.05). A positive correlation was found between DII and CADAS, as well as between CADAS and ASMC. FNS scores showed a negative correlation with CADAS only among female participants.ConclusionTo support healthy adolescent development and mitigate the risks posed by the digital age, it is recommended to design and implement comprehensive intervention programs based on school, family, and individual levels, utilizing multidisciplinary approaches.